Introducing the Ethiopian Agricultural Portal - Mekonnen, Fanos (International Livestock Research Institute, 2011)
Fanos Mekonnen introduces the Ethiopian Agricultural Portal that has been developed by IPMS and the Ethiopian government to increase access to information in the sector. She was speaking at the IPMS experience-sharing workshop on Market-Oriented Smallholder Development in Ethiopia, 2-3 June 2011 in Addis Ababa. The website is at http://www.eap.gov.et